Case report: “Fur stole and turtleneck” and “halter-back” signs: an expanded wardrobe for dermatomyositis - Ho, Jonathan D.; Burton, Andrew T. M.; McKenzie, Trimane; Best, Ciara; Clare-Lyn Shue, Andrea; Smith-Matthews, Stephanie; Fraser, Kimone; Anderson, Asana (Frontiers in Immunology, 2024)
A diagnosis of dermatomyositis requires recognition of distinct patterns of skin disease in combination with, and sometimes without, muscle weakness. Often, a striking contrast between involved and uninvolved areas is observed. Familiar patterns include eyelid and midfacial eruptions, Gottron papules/sign, and upper back (shawl sign), central chest (V/open collar sign), and lateral thigh (holster sign) involvement. More recently, new specific antibody/phenotype-associated patterns have been reported. We describe a case series of two distinct patterns of skin involvement in six adult patients with both classical and amyopathic dermatomyositis. Three had paraneoplastic disease. All had intermediate to richly pigmented skin; five were of Afro-Caribbean and one was of Asian-Caribbean descent. Four were men, and two were women. Ages ranged from 41 to 89 years. All patients had concomitant hallmark signs (facial, hand, and/or trunk signs). Three were amyopathic. The first pattern involved a sharply demarcated, horizontally oriented hyperpigmented patch/thin plaque across the shoulders and upper chest, extending up the anterior neck. The second was the combination of the classical upper back shawl distribution with distinct mid-back sparing and diffuse involvement of the lower back. Named patterns help with the recognition of skin rashes in dermatomyositis. Based on the current lexicon describing items of apparel, we liken the first pattern to a “fur stole and turtleneck” sign and the latter to a “halter-back” or “reflected-shawl” sign. Biopsies revealed hyperkeratosis and interface dermatitis, often with epidermal atrophy, compatible with dermatomyositis. These patterns perhaps represent the coalescence of already well-described signs, photo-exacerbation, koebnerization, mechanical stretch, and other currently unclear factors contributing to patterning in dermatomyositis. Pattern distribution recognition is particularly valuable in individuals with richly pigmented skin who may lack typical violaceous erythema. The distinct demarcation led to the initial misdiagnosis of allergic contact dermatitis or other exogenous dermatitis in most of our patients. Further work involves evaluation of antibody phenotype and internal involvement associations. Limitations include lack of specific antibody panels and longitudinal follow-up data.